Integration of structured cooperative learning in mathematics classrooms - Hossain, Md. Anowar; Kamel Ariffin, Muhammad Rezal (2018)
Cooperative learning model played a dynamic role in improving students’ achievement in mathematics. The purpose of this research study was to compare the effects of three instructional methods on students’ mathematics achievement and attitudes toward mathematics among secondary students in Natore, Bangladesh. These instructional methods were used to teach students in three experimental groups such as group 1 with structured cooperative learning, group 2 with unstructured cooperative learning and group 3 with conventional teaching. 105 students took part in the experiment and completed pre-test and post-test of mathematics achievement and attitudes toward mathematics. The statistical analysis such as ANOVA, MANOVA and post hoc pairwise comparison were used to analyze the data. The results showed a significant effect of structured cooperative learning on mathematics achievement and attitudes toward mathematics. The findings revealed that the structured cooperative students outperformed the unstructured cooperative and conventional students on mathematics achievement due to structured form of cooperative learning integration. Therefore, structured cooperative learning can successfully be implemented to promote students’ achievement in mathematics.